Remembering Professional Commitments: Trusting in Teachers - Bulman, Jeannie; Burnett, Cathy; Merchant, Guy; Rogers, Emma (Language and Literacy / Langue et littératie, 2021)
In England statutory expectations for literacy education place little emphasis on contemporary modes and media of communication and, as such, are out of step with contemporary life. We explore how open-ended, collaborative pedagogies can provide rich contexts for authentic everyday communication even in the context of such reductionist curriculum and assessment frameworks. This leads us to claim that the success of such approaches depends on the enthusiasm, experience and creativity of teachers and that remembering longstanding professional commitments in language and literacy teaching is at least as important as rethinking the curriculum when advocating for literacy provision more suited to current times.